ROLE OF SCHOOL LIBRARIES AND INFORMATION SERVICES IN PROMOTING BASIC EDUCATION IN JIGAWA STATE - Kwara, Gambo (International Journal of Psychosocial Rehabilitation, 2020)
Almost all civilizations recognized the fact that dissemination of information to the children is as important as to the adults; but unfortunately, children’s information needs have received very little attention in jigawa state.In this paper “Role of school libraries and information services in promoting basic education in jigawa state” we highlighted the significance of school libraries as a means of promoting basic education, with provision of adequate services and orientation to its clienteles. A school library is a stimulating place which both satisfies and arouses a desire for knowledge that provides new experiences. A basic education which evolve the programs and instruction that are intended to provide students with the opportunity to become responsible and respectful in their daily life, is hereby discussed. This study highlighted a number of contributions made by the school libraries toward effective basic education in jigawa state, such us user education, cataloguing and classification, library week, exhibition or display, reader’s advisory services etc. In view of the above summary, there is need for modern facilities to be provided in our school libraries to enhance the efforts made by the librarians in the task of promoting basic education in jigawa state.